1994
DOI: 10.1007/bf00188290
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic-assisted vagotomy and distal gastrectomy

Abstract: This is a report of the techniques used on and outcome for three patients who underwent laparoscopic-assisted vagotomy and distal gastrectomy for complicated peptic ulcer disease. The first patient had a Billroth I anastomosis in 2 h 42 min with an estimated blood loss of 200 ml. Oral fluids were started on day 3 and the diet progressed to a soft food by day 5. The patient was discharged 11 days after his gastrectomy following a transurethal prostatic resection on day 6. The second patient had a Billroth II an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

1996
1996
2002
2002

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…Indications for laparoscopic Billroth I gastrectomies are the same as for Billroth II gastrectomies. Technically, in most cases of Billroth I procedures, dissection and resection phases are carried out under the conditions of pneumoperitoneum, but the gastroduodenostomy is done by open technique through a small incision in the right upper quadrant [1,12]. Wedge resections can easily be performed with endostaplers and are mainly indicated in benign tumors of the stomach [9] and selected early gastric cancers [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indications for laparoscopic Billroth I gastrectomies are the same as for Billroth II gastrectomies. Technically, in most cases of Billroth I procedures, dissection and resection phases are carried out under the conditions of pneumoperitoneum, but the gastroduodenostomy is done by open technique through a small incision in the right upper quadrant [1,12]. Wedge resections can easily be performed with endostaplers and are mainly indicated in benign tumors of the stomach [9] and selected early gastric cancers [8].…”
Section: Discussionmentioning
confidence: 99%
“…Besides the totally intraperitoneal laparoscopic gastrectomy, laparoscopicassisted gastrectomy either by gasless technique (elevating the abdominal wall with U-shaped retractor) or insufflating the abdomen by CO 2 has been practiced by some authors [12]. The laparoscopic approach can now be extended to other related operations such as Billroth I gastrectomy, wedge resection, and total gastrectomy [1,7,10,[12][13][14].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, laparoscopic gastrectomy requires extension of the skin incision to retrieve the specimen. Based on several case reports, range of the wound size for specimen retrieval is from 25 mm to 50 mm [1,2,4,[6][7][8][9][11][12][13][14].…”
Section: Discussionmentioning
confidence: 99%
“…Goh et al [1 I], Anvari et al [2], and Fowler et al [6] reported several cases of laparoscopic gastrectomy with favorable results, but all of these were for benign gastric ulcers. The first case of laparoscopically assisted Billroth I gastrectomy for early gastric cancer with lymph node dissection was reported by Kinato et al [16].…”
mentioning
confidence: 99%